Tauhid Education in the Book Al-Ushul Ats-Tsalatsah by Muhammad bin Abdul Wahhab - Qomari, Vikri Aflaha; Satria, Rengga (EDUMALSYS Journal of Research in Education Management, 2023)
This research focuses on the values of tauhid education. The purpose of this study is to find out how monotheistic education is in the book Al-Ulshul Ats-Tsalatsah written by Muhammad Bin Abdul Wahhab. Tawhid is the most important teaching because it contains teachings about the pure and consequential acknowledgment of the oneness of Allah SWT and is a foundation and principle as a place for all deeds, and is to form monotheistic people. This research is a library research study, namely research that focuses on the discussion of literature related to research focus such as books that can be used as a reference source. The results of this study, researchers found the values of monotheism education in the book Al-Usul Ats-Tsalatsah written by Muhammad Bin Abdul Wahhab which contains three foundations, namely knowing Allah, knowing Islam, and knowing the Prophet Muhammad SAW.